2021
DOI: 10.3390/ani11061545
|View full text |Cite
|
Sign up to set email alerts
|

Appeasing Pheromones against Bovine Respiratory Complex and Modulation of Immune Transcript Expressions

Abstract: Bovine respiratory disease is still a major concern and has major economic impact. Another consequence of respiratory infections is the use of antimicrobial molecules to control bacterial pathogens. This can participate in the emergence and shedding of antimicrobial resistance that can threaten animal as well as human health. Appeasing pheromones with their capacity to reduce stress and thus their ability to preserve the functions of the immune system have been proposed to reduce the use of antimicrobial subst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In fact, a stressor, when perceived by the animal, might lead to the inflammatory cascade that acts as nutrient sink, removing the nutrients from an anabolic to a catabolic state [ 16 ]. Moreover, blood mRNA expression of pro-inflammatory-related genes was reduced following weaning and feedlot entry in animals that received BAS [ 87 ], demonstrating that the modulation of inflammation might be one of the mechanisms underlying the benefits observed by [ 85 ].…”
Section: Pheromones In Livestock Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a stressor, when perceived by the animal, might lead to the inflammatory cascade that acts as nutrient sink, removing the nutrients from an anabolic to a catabolic state [ 16 ]. Moreover, blood mRNA expression of pro-inflammatory-related genes was reduced following weaning and feedlot entry in animals that received BAS [ 87 ], demonstrating that the modulation of inflammation might be one of the mechanisms underlying the benefits observed by [ 85 ].…”
Section: Pheromones In Livestock Productionmentioning
confidence: 99%
“…In an ideal production setting, it would be interesting to investigate whether BAS administration at castration maintains similar performance when compared to non-castrated beef animals. Although positive results have been reported in beef cattle following different stressful procedures, more research is warranted to understand the underlying biological mechanisms, if more than reported by [ 87 ], by which BAS promotes an improvement in the performance and health of the beef cattle herd, more specifically in different stressor types. The potential benefits of administering BAS under a pathogen challenge are also worth mentioning, as this might be tightly connected to stressful situations, such as transport/feedlot entry and the occurrence of the bovine respiratory disease complex in the first 30 days on feed.…”
Section: Pheromones In Livestock Productionmentioning
confidence: 99%
“…Administering BAS to recently weaned calves in the present study decreased haptoglobin and NEFA concentrations, indicating and corroborating previous reports that BAS alleviates an acute-phase reaction and decreases mobilization of body tissues during a stress event ( Cappellozza et al, 2020 ; Colombo et al, 2020 ; Cooke et al, 2020 ; Schubach et al, 2020 ). Accordingly, a recent study by Hervet et al (2021) demonstrated that bulls administrated BAS had decreased blood mRNA expression of genes linked to pro-inflammatory processes after weaning and feedlot entry. According to the manufacturer, the BAS is estimated to remain in the animals for approximately 15 d after administration, which corroborates with the benefits on calf performance and the immune response observed by Cooke et al (2020) .…”
Section: Discussionmentioning
confidence: 99%